Effect of Hesperidin as an Adjunct to Scaling and Root Planing on Clinical Parameters and Serum C-Reactive Protein Level in Chronic Periodontitis: A Randomized, Triple-Blind, Placebo-Controlled, Clinical Trial - Supriya Shirodkar; Amit Vasani; Tanu Sahney; Meet Modi; Salini Pattnaik; P. Ravi Tejeshwar Reddy (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontitis is a chronic inflammatory disease that damages the supporting structures of the teeth, primarily caused by dental plaque containing Gram-negative bacteria. These bacteria trigger an inflammatory host response leading to tissue destruction. Materials and Methods: A total of 84 patients with moderate to severe chronic periodontitis were randomly assigned to either a test group receiving 500 mg of hesperidin daily or a control group receiving a placebo both alongside scaling and root planing (SRP). Clinical parameters including the gingival index (GI), sulcus bleeding index (SBI), probing depth (PD), and clinical attachment level (CAL) were evaluated at baseline, 3 weeks, and 6 weeks. Serum C-reactive protein (CRP) levels were measured at baseline and 3 weeks to assess systemic inflammation. Results: Of the 84 patients, 80 completed the study, with 60 males and 20 females. The test group showed significant reduction in serum CRP levels from baseline to 3 weeks (mean difference: 1.6300, P < 0.001), while the control group also showed a significant decrease (mean difference: -1.2730, P = 0.001). However, no statistically significant differences were found in clinical parameters (GI, SBI, PD, CAL) between the test and control groups at any time point. Intragroup analysis showed significant improvements in these parameters over time within both groups, indicating the effectiveness of SRP in managing clinical symptoms of periodontitis. Conclusion: Hesperidin significantly reduced serum CRP levels, indicating an anti-inflammatory effect, but did not result in significant improvements in clinical parameters compared to placebo.